2020
DOI: 10.1002/ana.25725
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Acute Blood‐Based Biomarkers for Sport‐Related Concussion

Abstract: Objective: Prospectively characterize changes in serum proteins following sport-related concussion and determine whether candidate biomarkers discriminate concussed athletes from controls and are associated with duration of symptoms following concussion. Methods: High school and collegiate athletes were enrolled between 2015 and 2018. Blood was collected at preinjury baseline and within 6 hours (early acute) and at 24 to 48 hours (late acute) following concussion in football players (n = 106), matched uninjure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 32 publications
2
68
0
Order By: Relevance
“…However, recent studies have shown that protein biomarker assays can detect even low levels of UCH-L1, S100B, and GFAP elevated after sport concussion not associated with CNS pathology detectable by computed tomography (CT) scans. 214,215 BBs have yet to be fully exploited for medical management of brain injury. However, as documented in Table 3, research laid the foundation for U.S. Food and Drug Administration (FDA) accelerated approval of measures of UCH-L1 and GFAP for acute diagnosis of TBI not associated with CT abnormalities versus moderate TBI associated with CT abnormalities.…”
Section: Use Of Blood Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have shown that protein biomarker assays can detect even low levels of UCH-L1, S100B, and GFAP elevated after sport concussion not associated with CNS pathology detectable by computed tomography (CT) scans. 214,215 BBs have yet to be fully exploited for medical management of brain injury. However, as documented in Table 3, research laid the foundation for U.S. Food and Drug Administration (FDA) accelerated approval of measures of UCH-L1 and GFAP for acute diagnosis of TBI not associated with CT abnormalities versus moderate TBI associated with CT abnormalities.…”
Section: Use Of Blood Biomarkersmentioning
confidence: 99%
“…However, recent studies have shown that protein biomarker assays can detect even low levels of UCH-L1, S100B, and GFAP elevated after sport concussion not associated with CNS pathology detectable by computed tomography (CT) scans. 214 , 215 …”
Section: Rationale For Studies Of Blood Biomarkers For Diagnosis Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, there have been two recent large prospective studies. 48,49 Concussed athletes have been shown to have significant elevations in GFAP, UCH-L1 and tau acutely post-injury, with a panel combining multiple biomarkers showing adequate discrimination for detection of sports-related concussion. 48 Similarly, while on a panel of biomarkers consisting of: GFAP, UCH-L1, S100B, alpha-II-spectrin breakdown product 150, interleukin 6, interleukin 1 receptor antagonist (IL-1RA), and c-reactive protein, all proteins aside from GFAP and CRP demonstrated discrimination of concussed patients from non-concussed contact sport controls.…”
Section: Biomarkersmentioning
confidence: 99%
“…48 Similarly, while on a panel of biomarkers consisting of: GFAP, UCH-L1, S100B, alpha-II-spectrin breakdown product 150, interleukin 6, interleukin 1 receptor antagonist (IL-1RA), and c-reactive protein, all proteins aside from GFAP and CRP demonstrated discrimination of concussed patients from non-concussed contact sport controls. 49 Early prognostic prediction can help plan tailored management strategy, both for the player and for the team, giving advanced notice of players unlikely to make a fast recovery and allowing for resource allocation. There have been various studies assessing the use of blood biomarkers for this purpose in the realm of sports concussion.…”
Section: Biomarkersmentioning
confidence: 99%